The Relationship Between Family Harmony and Aggressiveness in Grade 8 Junior High School Students in Sidoarjo: Hubungan Antara Keharmonisan Keluarga dengan Agresivitas pada Siswa Kelas 8 Sekolah Menengah Pertama di Sidoarjo - Dewanti, Ririn; Putra, Andhika Rahmat (Psikologia : Jurnal Psikologi, 2022)
Recently, cases of aggressiveness have been increasingly found in the mass media. This is very concerning. Family harmony is thought to be a factor triggering the criteria for aggressiveness in adolescents. The purpose of this study was to see the relationship between family harmony and aggressiveness in grade VIII students of SMP Negeri 1 Sukodono. The research will be conducted using a correlational quantitative approach. This study used sample 177 students who were obtained from random sampling techniques. The data collection technique was done using a psychological scale. Measurement using the Likert scale variable. Data were analyzed by conducting hypothesis testing using Pearson Correlaton Product Moment. The results of this study indicate that there is a significant relationship between family harmony and aggressiveness among students of SMP Negeri 1 Sukodono. High student family harmony will have an impact on aggressiveness, as well as a decrease in student family harmony with aggressiveness. The family harmony of SMP Negeri 1 Sukodono students is high, and the aggressiveness at SMP Negeri 1 Sukodono is low.